2007
DOI: 10.1073/pnas.0703166104
|View full text |Cite
|
Sign up to set email alerts
|

Internal DNA pressure modifies stability of WT phage

Abstract: dsDNA in bacteriophages is highly stressed and exerts internal pressures of many atmospheres (1 atm ‫؍‬ 101.3 kPa) on the capsid walls. We investigate the correlation between packaged DNA length in phage (78 -100% of WT DNA) and capsid strength by using an atomic force microscope indentation technique. We show that phages with WT DNA are twice as strong as shorter genome mutants, which behave like empty capsids, regardless of high internal pressure. Our analytical model of DNA-filled capsid deformation shows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
199
2
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(213 citation statements)
references
References 35 publications
11
199
2
1
Order By: Relevance
“…The hydration force is in this case nearly equal to the osmotic pressure of DNA inside the capsid. The strength of the capsid is optimized to the maximum osmotic pressure resulting from packaging the wild-type λ-DNA length [2]. However, the experimental data in ref.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…The hydration force is in this case nearly equal to the osmotic pressure of DNA inside the capsid. The strength of the capsid is optimized to the maximum osmotic pressure resulting from packaging the wild-type λ-DNA length [2]. However, the experimental data in ref.…”
Section: Introductionmentioning
confidence: 83%
“…In case of phage λ, it has been shown that the capsid strength approximately matches the force exerted by the DNA on the capsid walls [2,12]. This suggests that the capsid strength determines the maximum length of DNA that can be packaged, which in turn is also correlated with the strength of the packaging motor complex [2,13]. Therefore, investigating the mechanical properties of DNA-filled versus empty capsids is of great interest.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Like Michel et al [64], Ivanovska et al [38][39][40] have also used AFM to investigate the extent to which the genome of viral capsids contributes to the overall stiffness of the organism. They measured the mechanical properties of λ-phages that were either empty or filled with wild-type DNA to their full or a partial extent.…”
Section: Virusesmentioning
confidence: 99%